How green is my operation theater? - Nishant Kumar (Saudi Journal of Anaesthesia, 2014)
Objective: To ascertain the awareness regarding global warming and the anesthesia practices contributing to it in the city of Delhi. Materials and Methods: A questionnaire was circulated amongst the qualified anesthesiologists (consultants and senior residents) in the city of Delhi. The initial contact was made through e-mail and the questionnaire was required to be filled and returned electronically. The questionnaire was also made available online athttp: sites.google.com/site/surveydelhi. After 1 month, the forms were distributed physically. Assuming that at least 50% of the approximately 1200 practising anesthesiologists would be able to recognize the greenhouse gases correctly, the target number of responses was 150 with 99% confidence limit. Results: Of the 831 anesthesiologists contacted, only 184 responded. Ninety-eight percent were aware of the greenhouse effect, but only 15.8% (29) could correctly identify all the greenhouse gases. However, 47.28% (87) could identify nitrous oxide and inhalational agents as a cause of greenhouse effect. Ninety percent of the respondents use circle system and 87% use low flows frequently. Ninety-three percent (171) of respondents routinely use nitrous oxide, and 32.1% (59) would, however, not use air even if made available. Seventy-nine percent (145) advocated total intravenous anesthesia as an alternative to reduce the menace. Conclusion: Only 22% were motivated enough to respond to the survey. More than half of these anesthesiologists were not aware about the anesthetic agents contributing to the greenhouse effect. However, their clinical practices inadvertently do not add to the environmental pollution.